Reliability assessment of subsea pipelines under the effect of spanning load and corrosion degradation - Ben Seghier, M.E.A. (Elsevier B.V., 2022)
Subsea pipelines are delicate infrastructures with high importance to the oil and gas industry. These structures are surrounded by an extreme environment, in which free spanning is a major issue that can lead to several unwanted events such as local buckling or vortex-induced vibration. Moreover, corrosion is inevitable problem to these structures. All these problems highly reduce the safety levels of subsea pipelines. Hence, this paper proposes a new framework for the probabilistic analysis of subsea pipelines subjected to both free spanning and corrosion degradation. For the subsea pipeline, new limit state functions are developed that include failure modes due to corrosion degradation and spanning loads caused by the maximum bending stress. In addition, new probabilistic burst pressure models for corroded pipelines have been included, taking into consideration pipeline steel grade strength as well as the surrounding uncertainty. The importance sampling method is proposed to estimate the reliability analysis results in terms of failure probability and reliability index. The proposed framework is applied on a real case study of API 5 L X65 subsea pipeline. The impact of several parameters on the reliability analysis outcome are investigated and discussed through several scenarios. Results indicate the importance of early-inspection data for planning the suitable operating regime of the pipeline in terms of internal pressure, which can be used to estimate the allowable critical spanning lengths and corrosion defect geometries to alert the appropriate actions to avoid failures. Â© 2022 Elsevier B.V.